Technopower on Twitter platform - Tamara Tania Cohen Egler; Thiago Costa Pereira; Juan Manuel Salmenton; Diana Micheline Cohen (Cidades, Comunidades e Território)
The objective is to analyze the narratives flowing on Big Tech platforms that form social networks and define collective subjectivities. Therefore, research was carried out on the Twitter Platform with the aim of identifying its technical and social functioning, the formation of technological networks, the enunciation of narratives associated with political principles in the context of the elections for the Presidency of the Republic of Brazil, in 2022. The methodology developed in this study, as shown in this article, produces graphs that represent networks, and quantitative data on influencers, their narratives, tweets and retweets. To analyze the technopolitical network, it was necessary to examine two items. Firstly, the influencers’ physical dimension, including technical equipment, and mathematical data. Secondly, the social dimension involves the formation of techno-political networks associated with certain political events. To analyze how the polarization of society occurred, between the extreme authoritarian side and the democratic left side. Both fields produce a conflict associated with two conceptions of the world being carried out in a rhizomatic way in the world space. The analysis of technopolitical networks is urgent to illuminate public regulatory policies, in protection of democratic institutions and to focus on the formulation and implementation of public policies for the regulation of socio-technical networks, to place limits on the exercise of information technology corporations, their platforms and techno-political networks that are destroying the foundations of democracy.